STUDY OF COMPARISON AND CORRELATION OF QUALITY MANAGEMENT PRACTICES AND PERFORMANCE OF CENTRAL MUI MANAGERS BEFORE AND AFTER THE IMPLEMENTATION OF ISO 9001: 2015 - Trisna Ningsih Yuliati; Parwoto Parwoto; Ahmad Badawi Saluy (Dinasti Publisher, 2021)
This research was conducted to identify and analyze the Comparative Study of Quality Management Practices and Management Performance at Central MUI before and after ISO 9001: 2015 implementation and the relationship between Quality Management Practices and Management Performance before ISO implementation, the relationship between Quality Management Practices and Management Performance after ISO implementation. , The sampling method used was purposive sampling with a sample size of 100 respondents. Measurements were made using questionnaires and then the data were processed using SPSS software. This research was conducted at the central MUI. The results of this study indicate that Quality Management Practices before ISO and Quality Management Practices after ISO 9001: 2015 have a strong relationship in influencing the success of ISO 9001: 2015 which is implemented in the central MUI and the Performance of the Central MUI Management before ISO and the Performance of the Central MUI Administrators after ISO 9001 : 2015 has a very strong influence in influencing the success of ISO 9001: 2015 which is implemented at the central MUI. So it can be said that the Quality Management Practices and Performance Management at the Central MUI before and after the implementation of ISO 9001: 2015 have improved so that it needs to be maintained and maintained in order to stay good in implementing ISO 9001: 2015 which is implemented by the central MUI.